Temporal patterns of picoplankton abundance and metabolism on the western coast of the equatorial Atlantic Ocean - Maiara Menezes; Pedro C. Junger; Vinicius S. Kavagutti; Bruno Wanderley; Anderson de Souza Cabral; Rodolfo Paranhos; Fernando Unrein; André M. Amado; Hugo Sarmento (Ocean and Coastal Research)
Picoplankton are central global carbon (C) cycling players and often dominate the ocean plankton communities, especially in low latitudes. Therefore, evaluating picoplankton temporal dynamics is critical to understanding microbial stocks and C fluxes in tropical oceans. However, the lack of studies on low-latitude picoplankton communities translates into a common conception that there is an absence of seasonality. Herein, we studied the temporal variation in abundance (measured by flow cytometry), and carbon flux (taking bacterial production and respiration as proxies) of the picoplanktonic community for the first time, as well as their environmental drivers in a low-latitude (05° 59’ 20.7″S 035° 05’ 14.6″W) Atlantic coastal station. We performed monthly samplings between February 2013 and August 2016 in a novel microbial observatory – hereafter called the Equatorial Atlantic Microbial Observatory – established on the northeastern Brazilian Atlantic coast. Our results revealed stability in temporal dynamics of picoplankton, despite a considerable inter-annual variation, with some related to the El Niño (ENSO) event in 2015. However, weak environmental relationships found were not enough to explain the variation in picoplankton’s abundance, which suggests that other factors such as biological interactions may lead to picoplankton abundance variation over time. Heterotrophic bacteria dominated picoplankton during the entire study period and between photosynthetic counterparts, and Synechococcus showed greater relative importance than picoeukaryotes. These results bring a novel perspective that picoplankton may exhibit more pronounced fluctuations in the tropical region when considering inter-annual intervals, and is increasing prokaryotic contribution to carbon cycling towards the equator.